1997
DOI: 10.1116/1.589530
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid atomic force/scanning tunneling lithography

Abstract: We present a new technique for performing lithography with scanning probes that has several advantages over standard methods. This hybrid lithography system combines the key features of the atomic force microscope ͑AFM͒ and the scanning tunneling microscope ͑STM͒ by incorporating two independent feedback loops, one to control current and one to control force. We demonstrate a minimum resolution of 41 nm and nanometer alignment capabilities. This lithography system is capable of writing continuous features over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 24 publications
(20 reference statements)
0
21
0
Order By: Relevance
“…6,7 For example, one approach is to use an electrical bias on the scanning probe tip to generate field emission electrons. 8 The resulting localized electron beam exposes a resist covered sample, like in standard electron beam lithography, but without complex electron beam optics. Hence, high resolution lithography can be accomplished in a table top system.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 For example, one approach is to use an electrical bias on the scanning probe tip to generate field emission electrons. 8 The resulting localized electron beam exposes a resist covered sample, like in standard electron beam lithography, but without complex electron beam optics. Hence, high resolution lithography can be accomplished in a table top system.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that by reducing the size of this chip to a width of about 0.4 mm we could reduce the capacitance to below 600 fF. 6 Figure 2 shows the effect of the chip size of the voltage ramp. Here the setpoint current was changed abruptly from 0 to 50 pA at time tϭ0.3 s. Although the difference between the setpoint current and measured current ͑the error signal͒ was negligible, the measured current was purely capacitive during the voltage ramp.…”
Section: B Control Of the Emission Currentmentioning
confidence: 99%
“…Details are given in Ref. 6. After exposure, the wafer was given a postexposure bake ͑PEB͒ for 1 min at 115°C and developed in MF-322 for 10 min.…”
Section: Lithographymentioning
confidence: 99%
See 1 more Smart Citation
“…Within the last two decades, numerous tipbased nanofabrication methods have been developed, which use, e.g., thermo-mechanical interactions, 8 mechanical displacement such as nanoshaving/nanografting, 9 electric-fieldinduced deposition, 10,11 chemical modification by local anodic oxidation, 12 and local resist exposure by tip-emitted low energy electrons. 13,14 A more detailed overview about different SPL technologies can be found in Ref. 15.…”
mentioning
confidence: 99%